Molded carbon-ceramic brake disc and preparation method and application thereof

By treating the carbon fiber surface and mixing it with powder, the problems of long manufacturing cycle, high cost, and unstable performance of carbon ceramic brake discs have been solved, resulting in high-strength, low-cost, and highly uniform carbon ceramic brake discs suitable for automotive and other fields.

CN120817814AActive Publication Date: 2025-10-21HUNAN SHIXIN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202511083516.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-10-21
Estimated Expiration
2045-08-04

AI Technical Summary

Technical Problem

Existing technologies for preparing carbon-ceramic brake discs suffer from problems such as long preparation cycles, high costs, unstable performance, and uneven internal composition. In particular, when using short-fiber molded preforms, carbon fibers are easily corroded by silicon vapor, which affects mechanical properties.

Method used

The carbon fiber surface is treated with resin solution, which is sprayed while mixing to form a uniform protective layer. The molded preform is prepared by uniformly mixing the powder and additives, followed by carbonization and melt infiltration treatment to ensure uniform composition and stable performance.

Benefits of technology

A molded carbon ceramic brake disc with short preparation cycle, low cost and stable performance has been achieved, which is suitable for large-scale industrial production and has the characteristics of high strength, high temperature resistance and low porosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120817814A_ABST
    Figure CN120817814A_ABST
Patent Text Reader

Abstract

The invention discloses a mould pressing carbon ceramic brake disc and a preparation method and application thereof.The preparation method comprises the steps that continuous carbon fibers are chopped to obtain chopped carbon fibers, the chopped carbon fibers are mixed, resin glue liquid is sprayed while mixing is conducted, glue-coated carbon fibers are obtained, silicon-containing particles and auxiliaries are mixed to obtain mixed powder A, then the mixed powder A and resin powder are mixed to obtain mixed powder B, and the mixed powder B is added to the mould pressing carbon ceramic brake disc; and mixing the mixed powder B with the glue-coated carbon fibers to obtain a mixture, carrying out compression molding on the mixture to obtain a preform, carbonizing the preform to obtain a porous body, and siliconizing the porous body to obtain the composite material. According to the preparation method disclosed by the invention, the surface of the carbon fiber is treated by spraying a resin glue solution for the first time, a uniform protective layer is formed on the surface layer of the carbon fiber yarn, and an auxiliary agent is added into a mixture, so that a uniform capillary tube is formed when a preform is carbonized, the infiltration uniformity is promoted, and the uniformity of components, high density and low aperture ratio are ensured; therefore, the prepared molded carbon-ceramic brake disc is stable in performance, high in strength and resistant to high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molded carbon-ceramic brake disc and a preparation method and application thereof, belonging to the technical field of carbon-ceramic brake discs. Background Art

[0002] With the rapid development of the automotive industry in recent years, safe, lightweight, high-performance brake materials have become a research focus in the automotive braking field. Carbon-ceramic composites, due to their excellent characteristics such as wear resistance, high temperature resistance, low density, high strength, and stable friction performance, are widely used as the preferred material for the next generation of high-performance friction materials in the braking field.

[0003] At present, the main methods for manufacturing brake discs at home and abroad are long-fiber needle-punched preforms and short-fiber molded preforms. After high-temperature melt infiltration, the two preforms are machined to produce brake discs. The needle-punching method is to prepare the preform by needle-punching continuous carbon fibers into a preform, densify it through CVI / CVD, and then obtain a carbon ceramic blank through high-temperature melt infiltration. The long-fiber carbon ceramic disc is then machined. The carbon ceramic disc prepared by this method has good overall performance, but the preparation cycle is long, with the entire process taking more than 60 days. At the same time, the cost is high, and the uniformity of siliconization inside the product is poor. The short-fiber molded disc has a short preparation cycle, and the entire process can be completed within 30 days. The cost is low, but the molding density is low, and the carbon fibers are easily corroded by silicon vapor during melt infiltration, which reduces the mechanical properties of the carbon ceramic brake disc.

[0004] As described in CN116856171A, indeterminate-length carbon fibers are soaked in a modified solution to wet them, then removed from the modified solution and filtered to remove excess modified solution from the carbon fiber surface. This results in modified carbon fibers, which in turn are used to produce carbon-ceramic brake discs. These carbon-ceramic brake discs exhibit excellent mechanical and frictional properties. However, direct soaking of the carbon fibers makes it difficult to control the resin content and material uniformity. As described in CN115894060A, a preform is produced by needle-punching a carbon fiber fabric and a mesh layer layer by layer, and then by vapor deposition to form a carbon fiber base disc. While the resulting discs exhibit high compressive strength, the production process is long, energy-intensive, and costly. Therefore, molded carbon-ceramic brake discs with high strength, short cycle times, low energy consumption, and stable performance are attracting market attention. Summary of the Invention

[0005] In response to the problems of the prior art, the first objective of the present invention is to provide a method for preparing a molded carbon-ceramic brake disc. This method first treats the carbon fiber surface with a resin adhesive to produce a resin-coated carbon fiber with a uniform resin content. The resin-coated carbon fiber is then uniformly mixed with the surface-activated mixed powder in a three-dimensional mixer. The mixture is then placed in a mold for hot pressing and cooled to produce a molded preform. The molded carbon-ceramic brake disc is then produced through carbonization, melt infiltration, and finishing. This method features a short production cycle, low production costs, and uniform and stable internal composition, making it suitable for large-scale industrial production.

[0006] The second object of the present invention is to provide a molded carbon-ceramic brake disc prepared by the above preparation method.

[0007] The third object of the present invention is to provide an application of a molded carbon-ceramic brake disc prepared by the above preparation method.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] The present invention provides a method for preparing a molded carbon-ceramic brake disc, comprising chopping continuous carbon fibers to obtain chopped carbon fibers, mixing the chopped carbon fibers, spraying a resin adhesive while mixing to obtain rubber-coated carbon fibers, mixing silicon-containing particles with an additive to obtain mixed powder A, mixing the mixed powder A with resin powder to obtain mixed powder B, mixing the mixed powder B with the rubber-coated carbon fibers to obtain a mixture, pressing the mixture to obtain a preform, carbonizing the preform to obtain a porous body, and subjecting the porous body to siliconization treatment.

[0010] The resin glue consists of carbon powder, anhydrous ethanol and resin solution.

[0011] The present invention first uses resin glue to treat the surface of carbon fiber, and by mixing and spraying the resin glue, the carbon fiber and the resin glue are fully combined, forming a uniform protective layer on the surface of the carbon fiber filaments, thereby improving the performance consistency of the carbon-ceramic brake disc; after the resin glue is carbonized, the various components are stably and evenly covered on the surface of the carbon fiber filaments, avoiding corrosion of the carbon fiber by silicon; and adding an auxiliary agent to the mixture allows the preform to form uniform capillaries during carbonization, thereby promoting melt infiltration uniformity, ensuring component uniformity, high density, and low open porosity, thereby making the prepared molded carbon-ceramic brake disc stable in performance, high in strength, and high temperature resistance.

[0012] In the present invention, the order of adding materials is crucial. If an additive is added to the resin glue, the spraying effect will be reduced. However, by mixing the silicon-containing particles with the additive to obtain a mixed powder A, and then mixing the mixed powder A with the resin powder, a better mixing effect can be obtained. Finally, the resin powder further added can not only increase the carbon content, but also improve the bonding performance with the coated carbon fiber and improve the bonding performance between fibers.

[0013] In a preferred embodiment, the continuous carbon fiber is selected from T700 grade carbon fiber, preferably at least one of 12K T700 carbon fiber and 24K T700 carbon fiber.

[0014] A preferred solution is to cut the continuous carbon fiber into two parts, one of which is long fiber with a length of 15~30 mm, preferably 15~20 mm, and the other is short fiber with a length of 5~10 mm, preferably 8~10 mm, and the ratio of short fiber to long fiber is 1:1~4.

[0015] In the present invention, short-cut fibers are used in two lengths. Among them, shorter fibers can effectively improve the distribution of various fiber properties, but the mechanical properties are lower; longer fibers can improve the performance, but their anisotropy is poor, especially affecting the mechanical properties in the Z-axis direction. Through the synergy of the two fibers, the performance of the molded carbon-ceramic brake disc is ultimately optimized.

[0016] In a preferred embodiment, the resin glue solution comprises, by mass percentage, 8-20 wt% of carbon powder, 5-15 wt% of anhydrous ethanol, and 65-82 wt% of the resin solution.

[0017] In the actual operation process, the carbon powder, anhydrous ethanol and resin solution are fully stirred to obtain resin glue, and then the resin glue is sprayed while mixing during the mixing process to form a uniform protective layer on the surface of the carbon fiber filaments. After carbonization, the various components are stably and evenly distributed on the surface of the carbon fiber filaments to avoid corrosion of the carbon fiber by silicon. Of course, the various components of the resin glue need to be controlled within the above range. If there is too much carbon powder, it will cause internal defects in the product during molding. Too little will affect the carbon content, resulting in poor product performance after melt infiltration. Too much or too little resin solution will not only affect the wrapping effect of the carbon fiber filaments, but also too much or too little resin will cause resin carbon instability, affecting the performance after melt infiltration.

[0018] In a preferred solution, the carbon powder particle size is ≤10 μm, preferably 1-3 μm.

[0019] In a preferred embodiment, the carbon powder is selected from at least one of pitch coke powder, graphite powder, graphene, and carbon black.

[0020] In a preferred embodiment, the resin in the resin solution is selected from at least one of phenolic resin and furan resin.

[0021] Preferably, the solid content of the resin solution is 40-60%.

[0022] In a preferred embodiment, the mixing time is 15 to 30 minutes, and during the mixing process, the resin glue is sprayed in 4 to 5 times, with each spraying 20 to 30% of the total resin glue. This mixing and spraying method allows the resin glue to be most evenly distributed on the carbon fiber surface, achieving the best wrapping performance.

[0023] In a preferred embodiment, the silicon-containing particles are selected from silicon and / or silicon carbide.

[0024] In a preferred embodiment, the auxiliary agent is selected from at least one of calcium carbonate, magnesium carbonate, magnesium hydroxide and aluminum hydroxide.

[0025] In a preferred embodiment, the particle size of the additive is ≤10 μm, preferably 1-5 μm. Controlling the particle size of the additive within this preferred range optimizes performance. If the particle size is too large, silicon vapor will have difficulty filling the pores during infiltration, resulting in internal pores and poor performance. If the particle size is too small, no channels can be formed for silicon vapor to reach the product, and silicon vapor may remain confined to the surface during infiltration.

[0026] In a preferred embodiment, the mass ratio of the silicon-containing particles to the additive is 3.5-5.5:4.5-6.5.

[0027] In a preferred embodiment, silicon-containing particles are mixed with an additive to obtain mixed powder C, and a silane coupling agent is sprayed on the surface of the mixed powder C. After drying, the mixed powder A is obtained by grinding.

[0028] The silicon-containing particles and additives are modified by silane coupling agents and activated to reduce the degree of powder agglomeration. This not only makes the mixing more uniform, but also improves the interface bonding performance between the silicon-containing particles and the coated carbon fibers. In addition, there will be no delamination or cracking problems during the molding and carbonization processes. After carbonization, the additives decompose into gas to form uniform and continuous pores.

[0029] In the actual operation process, the silane coupling agent is evenly sprayed on the surface of the mixed powder C, and then baked in an oven for 2 hours. The dried mixed powder is ground into powder using a grinder to obtain mixed powder A.

[0030] Further preferably, the silane coupling agent is selected from at least one of KH550, KH560, KH570, A172 or A171.

[0031] Further preferably, the mass ratio of the silane coupling agent to the mixed powder C is 0.02-0.08:1.

[0032] In a preferred embodiment, the resin powder is selected from at least one of phenolic powder and furan powder.

[0033] In a preferred embodiment, the mass ratio of the mixed powder A to the resin powder is 4-6:4-6.

[0034] The materials are first mixed and modified with silicon-containing particles and additives, and then mixed with resin powder. The final materials are mixed most evenly. After the additives are decomposed, uniform and continuous pores are formed in the disk.

[0035] In a preferred embodiment, the mass ratio of the rubber-coated carbon fiber to the mixed powder B is 1:0.05-0.15, preferably 1:0.06-0.12.

[0036] By controlling the mass ratio of the rubber-coated carbon fiber to the mixed powder B within the above range, the final product is uniform, free of internal defects, and has optimal performance.

[0037] In actual operation, the surface-treated rubber-coated carbon fiber and the mixed powder B are stirred in an automatic liquid spray mixer for 15 minutes to be evenly mixed.

[0038] The preferred solution is to place the mixed material into the mold twice, place a ventilation slot-shaped mold core in the middle, and then press-form. Adding the mold core in the middle of the preform helps reduce the amount of prepreg used and shortens machining time.

[0039] In a preferred embodiment, the pressing temperature is 130-220° C., the pressing pressure is 1-10 MPa, and the holding time is 30-60 min.

[0040] In a preferred embodiment, the carbonization process is as follows: first heating to 200-400°C, preferably 300-400°C, and keeping warm for 2-3 hours, and then heating to 850-1100°C, preferably 900-1000°C, and keeping warm for 3-4 hours. The carbonization of the present invention is first heated to 200-400°C to further cross-link and strengthen the resin and release small molecular gases, and then heated to 850-1100°C to remove non-carbon elements and decompose the additives into gases. The carbonization and heating in the above two stages can not only improve the strength, but also form a uniform, through-internal pore structure, thereby improving the density and uniformity after siliconization.

[0041] In a preferred embodiment, the siliconizing treatment uses silicon powder and / or silicon alloy powder as a silicon source, the temperature of the siliconizing treatment is 1600-2200° C., and the time of the siliconizing treatment is 1-4 hours.

[0042] During the actual operation, the carbon ceramic disc surface after infiltration is ground, through-holes and assembly holes are processed, and subsequent testing, marking, assembly and other processes are completed to prepare the finished carbon ceramic brake disc.

[0043] The present invention also provides a molded carbon-ceramic brake disc prepared by the above preparation method.

[0044] The present invention also provides applications of the molded carbon-ceramic brake disc prepared by the above-mentioned preparation method, wherein the molded carbon-ceramic brake disc is applied to braking of automobiles, urban rail vehicles, motorcycles, unmanned aerial vehicles, and electric vertical take-off and landing aircraft.

[0045] The molded carbon-ceramic brake disc of the present invention has low cost and can be widely used in the automotive field for high-performance vehicles such as new energy vehicles, supercars, and racing cars.

[0046] The present invention adopts the above technical solution and has the following beneficial effects:

[0047] 1. This invention fully combines the carbon fibers with the resin adhesive through a series of processes, including spraying the carbon fibers with resin adhesive and stirring the adhesive while spraying. This forms a uniform protective layer on the surface of the carbon fibers, thereby improving the performance consistency of the carbon-ceramic brake disc. After the resin adhesive is carbonized, the various components are stably and evenly distributed on the surface of the carbon fibers, preventing silicon from corroding the carbon fibers and improving the performance of the carbon-ceramic brake disc.

[0048] 2. The addition of additives in the present invention allows the green body to form uniform capillaries during carbonization, which is beneficial to the uniformity of infiltration and improves the stability of the performance of the brake disc;

[0049] 3. Silicon-containing particles and additives are activated with coupling agents to reduce the degree of powder agglomeration, promote the interfacial bonding between the powder and the surface-treated carbon fibers, and reduce the risk of delamination and cracking during compression molding;

[0050] 4. The brake disc produced by the present invention has uniform component distribution, good performance consistency, low porosity, and consistent density and mechanical properties in different parts of the same product, and the mechanical properties of products of different specifications have little difference;

[0051] 5. The carbon-ceramic brake disc produced by the present invention has a short production cycle and low cost, and is suitable for large-scale industrial production. The carbon-ceramic brake disc produced by the present invention has the advantages of stable performance, high strength, high temperature resistance, and low porosity. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a cross-sectional view of the carbon-ceramic brake disc provided in Example 1.

[0053] Figure 2 This is a finished product picture of the carbon-ceramic brake disc provided in Example 1. DETAILED DESCRIPTION

[0054] The present invention will be further described below with reference to specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0055] Example 1

[0056] Step 1: Preparation of resin glue

[0057] Weigh 12 wt% of graphite powder with a particle size of 3 μm, 8 wt% of anhydrous ethanol, and 80 wt% of a phenolic resin solution, wherein the solid content of the phenolic resin solution is 50%, and stir them evenly with a blender to prepare a resin glue.

[0058] Step 2: Preparation of carbon fiber prepreg

[0059] The continuous carbon fiber was cut into two parts, one of which was a long fiber with a length of 15 mm and the other was a short fiber with a length of 10 mm. The short fibers of different lengths were weighed according to the mass ratio of long fiber:short fiber = 4:1. A three-dimensional mixer was used for uniform mixing. The uniform mixing time was 15 minutes. During the uniform mixing, the resin glue prepared in step 1 was sprayed onto the carbon fiber 5 times;

[0060] Step 3: Prepare mixed powder

[0061] Weigh 5wt% KH550 silane coupling agent and spray it evenly on the surface of 3μm silicon carbide and 5μm calcium carbonate particles in a mass ratio of 4:6. Bake in an oven for 2 hours and grind the dried ceramic powder into powder using a grinder.

[0062] The surface activated ceramic powder is then mixed with the resin powder in a mass ratio of modified ceramic powder: resin powder = 1:1 to prepare a mixed powder.

[0063] Step 4: Preparation of Molding Materials

[0064] Add the prepared mixed powder into step 2, according to the mass ratio of coated carbon fiber: mixed powder = 1:0.12, and then stir for 15 minutes using a three-dimensional mixer.

[0065] Step 5: Preparation of carbon fiber preform

[0066] The above molding material was weighed and placed in the mold twice, a ventilation slot-shaped mold core was placed in the middle part, and a hot press was used for molding. The molding temperature was 200°C, the molding pressure was 7 MPa, and the holding time was 40 min to prepare a preform.

[0067] Step 6: Carbonization of the preform

[0068] The preform obtained in step 5 is placed in a high-temperature carbonization furnace for carbonization. The temperature is first raised to 400° C. and kept at this temperature for 2 h, and then raised to 950° C. and kept at this temperature for 4 h to obtain a porous body.

[0069] Step 7: Infiltration of carbon / carbon porous body

[0070] The material prepared in step 6 is placed in a crucible and infiltrated with silicon powder at a temperature of 1700° C. for 2 h to obtain a carbon-ceramic composite material disk.

[0071] Step 8: Finishing of the carbon ceramic plate

[0072] The carbon ceramic disc surface after infiltration is ground, through-hole and assembly hole are processed, and subsequent testing, marking, assembly and other processes are completed to prepare the finished carbon ceramic brake disc.

[0073] Example 2

[0074] Step 1: Preparation of resin glue

[0075] Weigh 12 wt% of graphite powder with a particle size of 3 μm, 8 wt% of anhydrous ethanol, and 80 wt% of a phenolic resin solution, wherein the solid content of the phenolic resin solution is 50%, and stir them evenly with a blender to prepare a resin glue.

[0076] Step 2: Preparation of carbon fiber prepreg

[0077] The continuous carbon fiber was cut into two parts, one of which was a long fiber with a length of 20 mm and the other was a short fiber with a length of 8 mm. The short fibers of different lengths were weighed according to the mass ratio of long fiber:short fiber = 4:1. They were mixed in a three-dimensional mixer for 15 minutes. During the mixing period, the resin glue prepared in step 1 was sprayed onto the carbon fiber 4 times;

[0078] Step 3: Prepare mixed powder

[0079] Weigh 3μm silicon carbide: 5μm silicon: 5μm calcium carbonate in a mass ratio of 2:2:6, mix them evenly in a mixer, weigh 5wt% KH550 silane coupling agent, spray it evenly on the surface, bake it in an oven for 2 hours, and grind the dried ceramic powder into powder using a grinder;

[0080] The surface activated ceramic powder is then mixed with the resin powder in a mass ratio of modified ceramic powder: resin powder = 1:1 to prepare a mixed powder.

[0081] Step 4: Preparation of Molding Materials

[0082] Add the prepared mixed powder into step 2, according to the mass ratio of coated carbon fiber: mixed powder = 1:0.12, and then stir with a mixer for 15 minutes.

[0083] Step 5: Preparation of carbon fiber preform

[0084] The above molding material was weighed and placed in the mold twice, a ventilation slot-shaped mold core was placed in the middle part, and a hot press was used for molding. The molding temperature was 200°C, the molding pressure was 7 MPa, and the holding time was 40 min to prepare a preform.

[0085] Step 6: Carbonization of the preform

[0086] The preform obtained in step 5 is placed in a high-temperature carbonization furnace for carbonization. The temperature is first raised to 400° C. and kept at this temperature for 2 h, and then raised to 950° C. and kept at this temperature for 4 h to obtain a porous body.

[0087] Step 7: Infiltration of carbon / carbon porous body

[0088] The material prepared in step 6 is placed in a crucible and infiltrated with silicon powder at a temperature of 1700° C. for 2 h to obtain a carbon-ceramic composite material disk.

[0089] Step 8: Finishing of the carbon ceramic plate

[0090] The carbon ceramic disc surface after infiltration is ground, through-hole and assembly hole are processed, and subsequent testing, marking, assembly and other processes are completed to prepare the finished carbon ceramic brake disc.

[0091] Example 3

[0092] Step 1: Preparation of resin glue

[0093] Weigh 12 wt% of graphite powder with a particle size of 3 μm, 8 wt% of anhydrous ethanol, and 80 wt% of a phenolic resin solution, wherein the solid content of the phenolic resin solution is 50%, and stir them evenly with a blender to prepare a resin glue.

[0094] Step 2: Preparation of carbon fiber prepreg

[0095] Cut the continuous fiber into carbon fibers of different lengths, such as 8 and 20 mm, with a ratio of long fiber to short fiber of 1:1. Use a mixer to mix them evenly for 15 minutes. Spray the resin glue prepared in step 1 onto the carbon fibers in 4 batches.

[0096] Step 3: Prepare mixed powder

[0097] Weigh 3μm silicon carbide and 5μm magnesium carbonate in a mass ratio of 4:6, mix them evenly in a mixer, weigh 5wt% KH550 silane coupling agent, spray it evenly on the surface, bake it in an oven for 2 hours, and grind the dried ceramic powder into powder using a grinder;

[0098] The surface activated ceramic powder is then mixed with the resin powder in a mass ratio of modified ceramic powder: resin powder = 1:1 to prepare a mixed powder.

[0099] Step 4: Preparation of Molding Materials

[0100] Add the prepared mixed powder into step 2, according to the mass ratio of coated carbon fiber: mixed powder = 1:0.12, and then stir with a mixer for 15 minutes.

[0101] Step 5: Preparation of carbon fiber preform

[0102] The above molding material was weighed and placed in the mold twice, a ventilation slot-shaped mold core was placed in the middle part, and a hot press was used for molding. The molding temperature was 200°C, the molding pressure was 7 MPa, and the holding time was 40 min to prepare a preform.

[0103] Step 6: Carbonization of the preform

[0104] The preform obtained in step 5 is placed in a high-temperature carbonization furnace for carbonization. The temperature is first raised to 400° C. and kept at this temperature for 2 h, and then raised to 950° C. and kept at this temperature for 4 h to obtain a porous body.

[0105] Step 7: Infiltration of carbon / carbon porous body

[0106] The material prepared in step 6 is placed in a crucible and infiltrated with silicon powder at a temperature of 1700° C. for 2 h to obtain a carbon-ceramic composite material disk.

[0107] Step 8: Finishing of the carbon ceramic plate

[0108] The carbon ceramic disc surface after infiltration is ground, through-hole and assembly hole are processed, and subsequent testing, marking, assembly and other processes are completed to prepare the finished carbon ceramic brake disc.

[0109] Comparative Example 1

[0110] A method for preparing a molded carbon-ceramic brake disc, wherein the specific preparation steps are as described in Example 1, except that, in steps 1 and 2, the carbon fiber is not sprayed with resin glue, but is replaced with phenolic powder. An additive, carbon powder, and phenolic powder are physically mixed in equal proportions using a three-dimensional mixer. It is found that the carbon fiber easily pills and clumps, and the powder material agglomerates, making it difficult to mix evenly.

[0111] Comparative Example 2

[0112] A method for preparing a molded carbon ceramic brake disc, wherein the specific preparation steps are as described in Example 1, except that no additive is added. The density of the carbon ceramic disc is 1.78 g / cm3 when tested by vacuum method. 3 According to GB∕T 6569~2006, the bending strength of the carbon ceramic plate is 45.4MPa.

[0113] Comparative Example 3

[0114] A method for preparing a molded carbon-ceramic brake disc, wherein the specific preparation steps are as described in Example 1, except that the silicon-containing powder is not subjected to surface activation treatment. Cracks appear inside the product after infiltration. The density of the carbon-ceramic disc tested by vacuum method is 2.03 g / cm 3 According to GB∕T 6569~2006, the bending strength of the carbon ceramic plate is 59.1MPa.

[0115] Comparative Example 4

[0116] A method for preparing a molded carbon-ceramic brake disc, wherein the specific preparation steps are as described in Example 1, except that a mold core is not placed during molding, and ventilation grooves are dug in a machining center. It is found that 1.0 kg to 1.5 kg more raw materials are used, and the machining time is increased by 2 to 3 hours.

[0117] Comparative Example 5

[0118] Other conditions were the same as those in Example 1, except that during carbonization, the temperature was directly raised to 950° C. and kept at this temperature for 4 h. As a result, cracks appeared inside the obtained product.

[0119] Comparative Example 6

[0120] Other conditions were the same as those in Example 1, except that the carbon fiber prepreg was cut into 15 mm pieces.

[0121] The performance of the molded carbon-ceramic brake discs prepared in the examples and comparative examples was tested. The density of the carbon fiber prepreg was used. The bending strength of the carbon-ceramic discs was tested according to GB / T 6569-2006. The results are shown in Tables 1 and 2:

[0122]

[0123]

[0124] From the above, it can be seen that the density of the carbon ceramic brake disc prepared in the embodiment of the present application is 2.18~2.21g / cm 3 , with a low density and a porosity between 1.13% and 1.50%, indicating a significant additive effect, good infiltration, and a dense carbon-ceramic brake disc. The capillary tubes formed during carbonization serve as guides for siliconization, resulting in small and evenly distributed silicon particles infiltrating the disc, thereby improving the flexural strength of the carbon-ceramic brake disc. However, the comparative examples show that without surface treatment, the carbon fibers tend to settle to the bottom of the powder, resulting in uneven mixing and uneven siliconization of the disc, which in turn affects performance and reduces the disc's service life. Improper carbonization parameters and inappropriate carbon fiber prepreg length can also affect brake disc performance.

[0125] The above content specifically describes the method for preparing a carbon-ceramic brake disc and its application according to the present invention, which can be applied to fields such as automobile or rail transit braking. However, the present invention is not limited to the contents of the above specific embodiments. Therefore, any improvements, equivalent modifications or replacements based on the technical points of the present invention fall within the scope of protection of the present invention.

Claims

1. A method for preparing a molded carbon-ceramic brake disc, characterized in that: The continuous carbon fibers are chopped to obtain chopped carbon fibers, which are mixed and sprayed with resin glue while mixing to obtain rubber-coated carbon fibers; the silicon-containing particles are mixed with an additive to obtain a mixed powder A; the mixed powder A is then mixed with resin powder to obtain a mixed powder B; the mixed powder B is mixed with the rubber-coated carbon fibers to obtain a mixture; the mixture is pressed into a preform; the preform is carbonized to obtain a porous body; and the porous body is siliconized to obtain the obtained product; The resin glue consists of carbon powder, anhydrous ethanol and resin solution.

2. The method for preparing a molded carbon-ceramic brake disc according to claim 1, characterized in that: The continuous carbon fiber is selected from T700 grade carbon fiber; The continuous carbon fiber is cut into two parts, one of which is long fiber with a length of 15~30mm, and the other is short fiber with a length of 5~10mm, and the ratio of short fiber to long fiber is 1:1~4.

3. The method for preparing a molded carbon-ceramic brake disc according to claim 1, characterized in that: The resin glue solution comprises, by weight percentage, 8-20 wt% carbon powder, 5-15 wt% anhydrous ethanol, and 65-82 wt% resin solution; The carbon powder particle size is ≤10 μm; The carbon powder is selected from at least one of pitch coke powder, graphite powder, graphene, and carbon black; The resin in the resin solution is selected from at least one of phenolic resin and furan resin; The solid content of the resin solution is 40-60%; The mixing time is 15 to 30 minutes. During the mixing process, the resin glue is sprayed 4 to 5 times, with each spraying 20 to 30% of the total amount of the resin glue.

4. The method for preparing a molded carbon-ceramic brake disc according to claim 1, characterized in that: The silicon-containing particles are selected from silicon and / or silicon carbide; The auxiliary agent is selected from at least one of calcium carbonate, magnesium carbonate, magnesium hydroxide and aluminum hydroxide; The particle size of the auxiliary agent is ≤10 μm; The mass ratio of the silicon-containing particles to the additive is 3.5-5.5:4.5-6.

5.

5. The method for preparing a molded carbon-ceramic brake disc according to claim 4, characterized in that: The silicon-containing particles are mixed with an additive to obtain a mixed powder C, and a silane coupling agent is sprayed on the surface of the mixed powder C, dried, and ground to obtain a mixed powder A; The silane coupling agent is selected from at least one of KH550, KH560, KH570, A172 or A171; The mass ratio of the silane coupling agent to the mixed powder C is 0.02-0.08:1; The resin powder is selected from at least one of phenolic powder and furan powder; The mass ratio of the mixed powder A to the resin powder is 4-6:4-6; The mass ratio of the rubber-coated carbon fiber to the mixed powder B is 1:0.05-0.

15.

6. A method for preparing a molded carbon-ceramic brake disc according to any one of claims 1 to 3, characterized in that: The mixed material is placed in a mold twice, a ventilation slot-shaped mold core is placed in the middle part, and then pressed into shape; The pressing temperature is 130-220° C., the pressing pressure is 1-10 MPa, and the holding time is 30-60 min.

7. A method for preparing a molded carbon-ceramic brake disc according to any one of claims 1 to 3, characterized in that: The carbonization process is to first heat the material to 200-400° C. and keep the temperature for 2-3 hours, then heat the material to 850-1100° C. and keep the temperature for 3-4 hours.

8. The method for preparing a molded carbon-ceramic brake disc according to any one of claims 1 to 3, characterized in that: The siliconizing treatment uses silicon powder and / or silicon alloy powder as a silicon source, the temperature of the siliconizing treatment is 1600-2200° C., and the time of the siliconizing treatment is 1-4 hours.

9. A molded carbon-ceramic brake disc prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the molded carbon ceramic brake disc prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The molded carbon-ceramic brake disc is applied to braking of automobiles, urban rail vehicles, motorcycles, unmanned aerial vehicles, and electric vertical take-off and landing aircraft.

Citation Information

Patent Citations

  • Preparation method of carbon fiber brake disc

    CN115894060A

  • Preparation method of modified carbon fiber suitable for preparing carbon / ceramic brake disc by mould pressing process

    CN116856171A

  • Preparation method and application of near-size carbon-ceramic brake disc preform

    CN115849913A

  • High-strength carbon ceramic brake disc and preparation method thereof

    CN119390464A

  • High-strength short fiber carbon ceramic brake disc and preparation method thereof

    CN119490353A

Cited By

  • Preparation method of short fiber carbon-carbon composite material

    CN121717647A